Oh, brother-- Oh, sister : a sister's guide to getting along - Whitney, Brooks; Cornell, Laura (Middleton, WI : American Girl, 2008)
A girl's guide to getting along with siblings and surviving sticky situations, from teasing to tattling to sharing a room.
"Be your best"--Spine.
4.7
3-6
3-6
Keywords: Sisters -- Juvenile literature; Brothers and sisters -- Juvenile literature; Sibling rivalry -- Juvenile literature; Sisters; Brothers and sisters; Sibling rivalry; Sisters; Siblings; Sibling rivalry